Penguatan Nilai Budaya Minang “Sumbang Duo Baleh” Bagi Siswi Melalui Kegiatan Forum Annisa di MAN 2 Bukittinggi - Muhammad Nur Hadi Rasyid; Khairuddin Khairuddin; Jasmienti Jasmienti; Charles Charles (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
This research aims to understand and analyze the strengthening of Minang cultural values "Sumbang Duo Baleh" through the Annisa Forum at MAN 2 Bukittinggi. The research used a qualitative descriptive approach with the main informants namely the Annisa Forum supervisor and supporting informants such as curriculum representatives and Annisa Forum students. Data was collected through observation, interviews and documentation, then analyzed using data reduction techniques, data presentation and data withdrawal, as well as using triangulation to ensure the validity of the data. The research results show that the Annisa Forum has succeeded in strengthening Minang cultural values, especially in the aspects of Sumbang Kato, Sumbang Bagaua, and Sumbang Kurenah. Supporting factors in its implementation include support from the government, community, parents, school environment and peers, while the inhibiting factor is the lack of motivation from the students themselves.